Impact of supervisors' safety violations on an individual worker within a construction crew. (December 2019) - Liang, Huakang; Zhang, Shoujian
Highlights: In most previous studies on the vertical impact of supervisors on individual workers' safety behaviours, scholars focused primarily on supervisors' positive leadership styles and managerial skills. However, there has been limited research on the impact of supervisors' negative aspects, especially the social contagion effect of their safety violations during task implementation. Despite arguments that the formation of an unsafe behavioural norm within a construction crew is at least partly due to supervisors' influence (Conchie et al., 2013; Vicki Kaskutas et al., 2013), this is the first study to provide empirical evidence of the social contagion effect of supervisors' safety violations on individuals. Therefore, this research can provide some meaningful insights into how to further prevent safety violations in the construction industry. Abstract: Safety violations are prevalent on a construction site; thus, it is necessary to understand the supervisory practices that facilitate the propagation of these behaviours. This research explores this phenomenon by investigating an integrative model regarding the social contagion effect of supervisors' safety violations within a construction crew. The findings indicate that individuals are more likely to break safety rules when perceiving their supervisors' safety violations. This research distinguishes between situational and routine safety violations. Specifically, supervisors' situational safety violations are more socially contagious than their routine safety violations. Furthermore, supervisors' situational safety violations have indirect effects on individuals, mainly through leader–member exchange and workers' safety involvement. By contrast, supervisors' routine safety violations have indirect effects on individuals, mainly through management safety commitment and enforcement of safety rules and procedures. In addition, workers with a low education level are more likely to perform situational safety violations, whereas workers lacking work experience are more inclined to perform routine safety violations. Theoretical and practical implications and associated research limitations are also discussed in this paper.